FACTORS AFFECTING AUDIT DELAY IN MANUFACTURING COMPANIES IN THE CONSUMPTION GOODS INDUSTRY SECTOR - Enda Noviyanti Simorangkir; Frans Charles Pardede; Clara Nurcahaya Sitinjak; Geby Putri Abel Hutabarat; Zahwa Ardila; Putri Wahyuni (Jurnal Ipteks Terapan, 2023)
The purpose of this study was to determine the factors that influence audit delay in manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange. The population in this study were 73 companies. The sampling method used purposive sampling method and obtained a sample of 37 companies with observational data of 111 companies. The Independent Variables used are: Company Size, Profitability, Audit Opinion, and Leverage, while the Dependent variable used is Audit Delay. The research data was obtained from the annual financial reports of manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange for the 2019-2021 period. The analytical method used is a quantitative method by testing the classical assumptions. The results of the study show that company size and leverage have a significant effect on audit delay. While profitability and audit opinion have no significant effect on audit delay. Simultaneously Company Size, Profitability, Audit Opinion, and Leverage have a significant effect on Audit delay in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2019-2021.